1999
DOI: 10.1088/0741-3335/41/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of charge-exchange processes on x-ray spectra in TEXTOR tokamak plasmas: experimental and theoretical investigation

Abstract: Time-resolved high-resolution soft x-ray spectra from gas-puff injected Ar impurity ions have been investigated for neutral beam heated and ohmically heated discharges in the TEXTOR tokamak. The experimental spectra show systematic deviations from corona model calculations for the line intensities of the forbidden He-like lines x, y, z and the Li-and Be-like dielectronic satellite spectra: theoretical corona model calculations predict intensities significantly too low. High-intensity Li-like inner-shell excite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…Emission lines of Li-like ions have been observed in the spectra of a variety of astrophysical [1]- [2] and laboratory plasmas [3]- [4]. Similarly, high gain lengths have been measured in lasing plasmas, particularly for the 3d-4f transitions of Al XI and Si XII [5] in the soft x-ray region.…”
Section: Introductionmentioning
confidence: 89%
“…Emission lines of Li-like ions have been observed in the spectra of a variety of astrophysical [1]- [2] and laboratory plasmas [3]- [4]. Similarly, high gain lengths have been measured in lasing plasmas, particularly for the 3d-4f transitions of Al XI and Si XII [5] in the soft x-ray region.…”
Section: Introductionmentioning
confidence: 89%
“…In fact, a self-consistent analysis of the particle transport and charge exchange (including also charge exchange from excited states) with a self-consistent multilevel collisional-radiative approach has shown that charge exchange phenomena, particle transport and atomic data are very closely related, as proved for the argon spectra in Ref. [33].…”
Section: Figurementioning
confidence: 87%
“…At present, o/ot = 0 is assumed and the system Eq. (1) is closed by normalization conditions (for more details see [10,11]):…”
Section: Simulation Of Helium Emission: Diffusion and Radiation Transmentioning
confidence: 99%